Analisis Perilaku Herding Berdasarkan Kondisi Pasar Dengan Asimetri Informasi Sebagai Variabel Pemoderasi - Sugiantara, Putu Wira (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p13, 2022)
The research aims to detect the occurrence of herding behavior as a whole as well as in up market conditions or down market conditions. The study added information asymmetry as a moderating variable. This study uses the Cross Sectional Absolute Deviation (CSAD) method. The total sample in this study was 661 companies with 242 days of observation. The results of this study found that generally in 2020 herding occurred on the Indonesia Stock Exchange. Herding was also found in up market conditions but different things were found in down market conditions, namely herding was not found. Interestingly, this study found that information asymmetry is a moderating variable that strengthens the occurrence of herding. Keywords: Herding; Up and Down Market Condition; Information Asymetri .